2016
DOI: 10.1111/cpr.12286
|View full text |Cite
|
Sign up to set email alerts
|

PTH/SDF‐1α cotherapy promotes proliferation, migration and osteogenic differentiation of human periodontal ligament stem cells

Abstract: PTH/SDF-1α cotherapy promoted proliferation, migration and osteogenic differentiation of PDLSCs in vitro. Cotherapy seemed to have potential to promote periodontal tissue regeneration by facilitating chemotaxis of PDLSCs to the injured site, followed by promoting proliferation and osteogenic differentiation of these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 48 publications
3
33
0
2
Order By: Relevance
“…In the present study, we discovered that the expression of Runx2 was decreased post-MP treatment, whereas it was upregulated after the transplantation of SDF-1α-GFP-BMSCs, which is consistent with the results of previous studies [52, 53]. Lingqian et al reported that the cotherapy with the parathyroid hormone (PTH) and SDF-1 promoted osteogenic differentiation of human periodontal ligament stem cells by enhancing OCN expression and ALP activity [54], which is in line with the findings of the present study. Osteoblast differentiation is key to bone formation, in which bone morphogenetic protein-2/Smad signaling pathway is involved [55].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we discovered that the expression of Runx2 was decreased post-MP treatment, whereas it was upregulated after the transplantation of SDF-1α-GFP-BMSCs, which is consistent with the results of previous studies [52, 53]. Lingqian et al reported that the cotherapy with the parathyroid hormone (PTH) and SDF-1 promoted osteogenic differentiation of human periodontal ligament stem cells by enhancing OCN expression and ALP activity [54], which is in line with the findings of the present study. Osteoblast differentiation is key to bone formation, in which bone morphogenetic protein-2/Smad signaling pathway is involved [55].…”
Section: Discussionsupporting
confidence: 91%
“…39 As displayed in Figure 4B, the number of calcium nodules in the experiment group exposed to TDNs for 2 weeks was remarkably higher than that in the blank group without exposure to TDNs ( Figure 4B). 39 As displayed in Figure 4B, the number of calcium nodules in the experiment group exposed to TDNs for 2 weeks was remarkably higher than that in the blank group without exposure to TDNs ( Figure 4B).…”
Section: Enhancement Of Calcium Nodule Formation and Alp Activitymentioning
confidence: 81%
“…The extracted teeth were transported from the clinic to the laboratory in Dulbecco's modified Eagle's medium (DMEM, Hyclone, Logan, UT, USA) with 5% antibiotics (100 U/mL of penicillin, 100 mg/mL of streptomycin, Sigma‐Aldrich, St Louis, MO, USA). PDL tissue from the middle third of the root surface was collected, and single cell of PDLSCs was acquired according to our previous study . PDL tissue was cut into small pieces and digested with 3 mg/mL collagenase I (Sigma‐Aldrich) and 4 mg/mL dispase II (Invitrogen, Carlsbad, CA, USA) for 40 minutes at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…PDL tissue from the middle third of the root surface was collected, and single cell of PDLSCs was acquired according to our previous study. 33 In brief, cells were incubated with DMEM containing 10 μL test reagents for 2.5 hours at 37°C. The absorbance was measured at a wavelength of 450 nm with a microplate reader (SPECTROstar Nano, BMG Labtech, Offenburg, Germany).…”
Section: Cell Isolation and Cultivationmentioning
confidence: 99%